Adjuvant treatment of hepatocellular carcinoma after orthotopic liver transplantation: do we really need this?. (6th December 2012) - Fujiki, M.; Aucejo, F.; Kim, R.
Abstract Hepatocellular carcinoma (HCC) continues to rise and is still a major cause of mortality. Orthotopic liver transplantation (OLT) continues to give patients the best chance for cure, but recurrence of the disease remains a problem. Even with the implementation of the Milan criteria, recurrence rates have been shown to be 8–15% in most studies and even higher in patients who are beyond the Milan criteria. Therefore, several investigators have looked into the value of adjuvant therapy using systemic cytotoxic chemotherapy in HCC after OLT. Unfortunately, most of the trials are very small, and the results have been disappointing. But trials using Licartin seem to be promising, and other drugs such as FOLFOX and sorafenib warrant further investigation based on their efficacy in the advanced disease. In this review, we will review the current data on efficacy and rationale of adjuvant treatment for HCC after OLT including novel biomarkers.